Fra scenerne IV og V: Det andet uddrag fra det første udkast til “Mellem hånden og munden” noget foreløbigt til en teori om kunstnerisk forskning gennem tre cifre – del I, 1972-73 - Day, James (Peripeti, 2021)
‘From scenes IV and V’ picks up the search for a preliminary theory of artistic research in and around the years 1972-73, via readings of Peter Weiss’ three-volume novel, The Aesthetics of Resistance and the movie Nightcleaners, shot by the Berwick Street Collective. Practices of artistic research, determined as practices that encourage new forms of cognition through which the possibility for revolution can be ventilated, are suggested to be a dialectical process that articulates its conditions of possibility via investigations of the direct process of its production.